Descriptions of two new species of the family Scythrididae from Europe (Lepidoptera: Scythrididae) - K. Nupponen; N. Savenkov (SHILAP, 2019)
Two new species of the family Scythrididae are described from Europe: Scythris spiniferella Nupponen & Savenkov, sp. n. from Southern Spain, and Scythris rowecki Nupponen & Savenkov, sp. n. from the Southern Ural Mountains, Russia. The former taxon belongs to the schleichiella species-group, and the latter one is related to the canescens species-group s. l. The external appearance of the adult and the genitalia of the new species are illustrated.